2020
DOI: 10.1063/5.0006684
|View full text |Cite
|
Sign up to set email alerts
|

Laser-induced fluorescence measurement of very slow neutral flows in a dusty plasma experiment

Abstract: Laser-Induced Fluorescence (LIF) provides the temperature and flow velocity of a target species by direct measurement of its velocity distribution via Doppler Shift. A LIF diagnostic has been developed at the Caltech Water-Ice Dusty Plasma Experiment that uses an ultra-narrow tuneable diode laser to pump the λ vac = 696.735 nm argon neutral transition. A photomultiplier detects fluorescence emission at λ vac = 772.633 nm. Signal to noise ratios in excess of 100 are achieved along with a high degree of reproduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…This saturation of α can be seen from the terms containing λ becoming unimportant in Equations (41)-(43) when l b . 3  For the Caltech experiment t ref =8 ms, so the prediction that α is constant for times much greater than 8 ms isconsistent with Figure 4(b) in Marshall & Bellan (2020), which shows the aspect ratio remaining constant at α≈4.5 when a increases from 20 to 80 μm in a 10 s time interval.…”
Section: Modelmentioning
confidence: 81%
“…This saturation of α can be seen from the terms containing λ becoming unimportant in Equations (41)-(43) when l b . 3  For the Caltech experiment t ref =8 ms, so the prediction that α is constant for times much greater than 8 ms isconsistent with Figure 4(b) in Marshall & Bellan (2020), which shows the aspect ratio remaining constant at α≈4.5 when a increases from 20 to 80 μm in a 10 s time interval.…”
Section: Modelmentioning
confidence: 81%
“…[214][215][216]220] Laser-absorption measurements by Pikalev et al [125] show only the evidence of dust-induced gas heating. Marshall et al [157] showed that the LIF measurements suffer from problems with the laser power broadening and absorption of the laser light on its way through the plasma. Solution of these problems could help to directly measure the neutral gas temperature field in a plasma and make a further step in understanding of the dust-induced effects on it.…”
Section: Discussionmentioning
confidence: 99%
“…Application of laser spectroscopy to the investigations of dust-plasma interactions does not have a long history. Nevertheless, several works have been performed on 1s 5 argon metastable atoms [125,149,[157][158][159] and 1s 3 neon metastable atoms. [155] One of the unsolved problems that could lead to significant progress in the investigations of the dust-plasma interactions is the measurement of ion velocity distributions.…”
Section: Laser Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…3 ¯ For the Caltech experiment t ref =8 ms, so the prediction that α is constant for times much greater than 8 ms isconsistent with Figure 4(b) in Marshall & Bellan (2020), which shows the aspect ratio remaining constant at α≈4.5 when a increases from 20 to 80 μm in a 10 s time interval.…”
mentioning
confidence: 81%